2012
DOI: 10.1088/0143-0807/33/5/1301
|View full text |Cite
|
Sign up to set email alerts
|

An inventory on rotational kinematics of a particle: unravelling misconceptions and pitfalls in reasoning

Abstract: Student difficulties regarding the angular velocity () and angular acceleration () of a particle have remained relatively unexplored in contrast to their linear counterparts. We present an inventory comprising multiple choice questions aimed at probing misconceptions and eliciting ill-suited reasoning patterns. The development of the inventory was based on interactions with students, teachers and experts. We report misconceptions, some of which are parallel to those found earlier in linear kinematics. Fixation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 16 publications
1
44
0
Order By: Relevance
“…Yet, kinematics is an essential basis for understanding the entire domain of mechanics and of the later physics curriculum as it provides conceptual and mathematical foundations for all areas of physics (e.g., concept of force, momentum and energy, symmetry and conservation principles, etc.). For example, misconceptions regarding rotational motion are directly related to improper understanding of linear kinematics [10].…”
Section: A Mrs In General and In Kinematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, kinematics is an essential basis for understanding the entire domain of mechanics and of the later physics curriculum as it provides conceptual and mathematical foundations for all areas of physics (e.g., concept of force, momentum and energy, symmetry and conservation principles, etc.). For example, misconceptions regarding rotational motion are directly related to improper understanding of linear kinematics [10].…”
Section: A Mrs In General and In Kinematicsmentioning
confidence: 99%
“…The development started with a literature review on existing test instruments related to representations and kinematics [4,7,[10][11][12]. Findings of physics education research concerning MRs had a strong influence on the test structure.…”
Section: A Developmentmentioning
confidence: 99%
“…Ortiz et al (2005) also found out that students experienced difficulties regarding 1) distinguishing between torque and force, and, 2) interpreting the definition of torque τ ≡ r × F primarily determining the practical vector point of force towards a particular axis (r). Mashood & Singh (2012) found out that students had difficulties in determining the speed and direction of the angular acceleration of the pendulum swinging. Students also believed that the direction of the vector ω and α are in the direction of motion of a body.…”
Section: Introductionmentioning
confidence: 99%
“…lar acceleration and momentum). 3,4 The current study proposes a physical model to teach the angular velocity vector. The setup described in this study can present a more tangible visualization of the angular velocity vector than the righthand rule allows.…”
Section: Contribution Of the Activity To Instructionmentioning
confidence: 99%